PRESERVAÇÃO DO GATO-DO-MATO NA REGIÃO DO ALTO URUGUAI - Hübner, Paulo Roberto; Link, Dionísio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The current work has the purpose of making the population from Alto Uruguai aware of thepreservation of the wild cat. Thereunto, practical actions were performed following themethodology of action research and aiming to reduce the conflicts between farmers and thespecies of little spotted cat (Leopardus tigrinus) and margay (leopardus wiedii). The conflict is themain factor of the wild felines slaughter which are obligated to hunt for food close to theresidences because of the deforestation and the constant forest fires. This work was developedwith the collaboration of a group of youths from the Scout Movement in Erechim/RS whoparticipated actively as social agents in the process of development of the actions and theresearch with large publicity in the local and regional press. With the results of the action researchit was possible to verify a sensitization process and also the comprehension of the habits andcharacteristics of these species, mainly the importance of them for the biotic chain. Nevertheless,there are established cultural processes about the felines hunt which demand time to be modified.The research is concluded recognizing the importance of the Environmental Education Projects associated with practical actions in order to make a true cultural change happen and enabling apeaceful acquaintance of humans with wild cats.